2016
DOI: 10.1016/j.electacta.2016.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Monocopper complex based on N-tripodal ligand immobilized in a Nafion® film for biomimetic detection of catechols: Application to dopamine

Abstract: complex based on Ntripodal ligand immobilized in a Nafion® film for biomimetic detection of catechols: Application to dopamine. Electrochimica Acta, Elsevier, 2016, 221, pp.80-85 AbstractA complex based on bis-pyrazolyl N-tripodal ligand known to present a good catalytic activity for the oxidation of 3,5-di-tert-butylcatechol is used to prepare a novel biomimetic sensor for the determination of catechol derivatives. The modified electrode prepared by encapsulation of the complex in a Nafion ® film leads to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…On the other hand, Zen et al and Boulkroune et al presented dopamine sensors that do not require the addition of hydrogen peroxide to a buffer [ 53 , 54 ]. In both cases, oxidation of dopamine is performed by forming an intermediate copper (II)-o-quinolate complex (Fig.…”
Section: Copper and Copper Oxidementioning
confidence: 99%
“…On the other hand, Zen et al and Boulkroune et al presented dopamine sensors that do not require the addition of hydrogen peroxide to a buffer [ 53 , 54 ]. In both cases, oxidation of dopamine is performed by forming an intermediate copper (II)-o-quinolate complex (Fig.…”
Section: Copper and Copper Oxidementioning
confidence: 99%
“…The dependence of the electrochemical signal on the concentration of 4-nitrophenylacetic acid was examined by cyclic voltammetry on four different (C 5 H 5 ) 2 Ti IV (OH 2 ) 2 2+ -modified electrodes and is given in Figure 3. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 A c c e p t e d M a n u s c r i p t The limit of detection (3  the standard deviation of five blank determinations) was determined from: 19 St-Sb ≥ 3σ (5) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 ...…”
Section: Electrolytementioning
confidence: 99%
“…The term "enzyme-less biosensor" has been previously attributed to this kind of sensor. 19 We have previously reported the interest of titanocene dichloride ((C 5 H 5 ) 2 TiCl 2 ) for the electrochemical reduction of biorecalcitrant pesticides containing a nitro group. 20 We have also shown that it keeps its catalytic activity when immobilized on graphite felt electrodes by encapsulation in a Nafion film.…”
mentioning
confidence: 99%
See 2 more Smart Citations